A scheme for stimulating message relaying cooperation - Haifeng Lin; Fuquan Zhang (International Journal of Distributed Sensor Networks)
It is expected that all the nodes try their best to store and forward the messages in the intermittent connection network. However, due to the limited resources, such as memory, power, and transient communication chance, selfish nodes may relay the messages without responsibility. Stimulating selfish to behave normally could improve network performance. However, usually, it is difficult to distinguish the selfish behavior from the inability to relaying the message. By monitoring the behavior of relay nodes that messages are forwarding through, this article proposes a scheme that relays messages according to the reputation of intermediate nodes. The proposed reputation estimation scheme combines selfish behavior and inability behavior, and reveals very little private information for the protocol practice. There is a trade-off between the threshold and the performance. Too low value may not distinguish the selfish nodes. On the contrary, some normal nodes may excluded and cannot join the relaying and processing. Simulation effectively demonstrates that the reputation affects the node’s performance, and an appropriate reputation threshold value is useful for improving the network performance.